Victim-Survivors’ Prioritization of Reasons for Non-Reporting Adult Sexual Assaults to Law Enforcement - Johnson, Ingrid Diane (Journal of interpersonal violence, 2023)
Despite the potential benefits of reporting a sexual assault to the police, few sexual assault victim-survivors choose to do so. Prior research on reasons for non-reporting has lacked American Indian/Alaska Native representation as well as a quantitative prioritization of non-reporting reasons. This study sought to fill those gaps by using quantitative data from 95 participants in an online, self-administered survey of victim-survivors of adult sexual assaults in Alaska. Descriptive, univariate results revealed great variation in the reasons for non-reporting. Further, which reasons were more commonly endorsed changed when measuring victim-survivor prioritization of reasons (primary, secondary, and tertiary) rather than simple endorsement. Lastly, there were few subgroup differences when conducting bivariate analyses using racial/ethnic identity and the act of reporting other adult sexual assaults in Alaska. The results of this study add to existing literature on non-reporting with an emphasis on changing how we measure the reasons behind non-reporting. The results also signal to criminal justice policy makers and practitioners that proactive, comprehensive efforts must be made to regain the faith and trust of current and potential victim-survivors so that they see the criminal justice system as a viable avenue for securing justice in ways that are meaningful to them.